EVALUATING THE IRON DEFICIENCY ANEMIA IN TYPE-II DIABETIC PATIENTS TAKING METFORMIN AND ITS ASSOCIATION WITH OXIDATIVE STRESS - ASIF, M; BANO, N; ASIF, U; NASIR, S; SHEHBAZ, L; IQBAL, MJ (Biological and Clinical Sciences Research Journal, 2024)
Iron deficiency anemia (IDA) is one of the most common nutritional disorders worldwide, affecting individuals across various demographic groups. Objective: The main objective of the study is to find iron deficiency anemia in type-II diabetic patients taking metformin and its association with oxidative stress. Methods: This cross-sectional observational study was conducted at the outpatient department (OPD) of the Medical Unit at Khawaja Muhammad Safdar Medical College, Sialkot, during the study period from 1st January 2024 to 31st June 2024. Data were collected from 285 patients diagnosed with type 2 diabetes mellitus (T2DM) who were receiving metformin therapy. Patients were divided into two groups—Group A (patients with IDA) and Group B (patients without IDA)—and the oxidative stress markers were compared between these two groups. Results: Data were collected from 285 patients with 92 in Group A (IDA) and 193 in Group B (Non-IDA). The mean age of participants was 57.6 ± 9.4 years, with no significant difference between Group A (58.2 ± 9.1) and Group B (57.3 ± 9.6) (p = 0.422). Gender distribution was similar between groups (p = 0.601). The mean duration of diabetes was also comparable between the groups (8.3 ± 3.4 years in Group A and 8.0 ± 3.1 years in Group B, p = 0.572). However, HbA1c levels were significantly higher in Group A (8.3 ± 1.6%) compared to Group B (7.5 ± 1.3%) (p = 0.012), indicating poorer glycemic control in the IDA group. Conclusion: This study concludes that iron deficiency anemia (IDA) is prevalent among type 2 diabetic patients on metformin therapy, affecting approximately one-third of the study population. Additionally, there is a significant association between IDA and increased oxidative stress, as evidenced by elevated levels of malondialdehyde (MDA) and reduced antioxidant enzymes (SOD and GPx) in patients with anemia.